Natural Resources, National Accounting and Economic Depreciation - John M. Hartwick (Queen's University, Department of Economics, 1990)
The current value Hamiltonian in an aggregate optimal growth problem with heterogeneous capital stocks including exhaustible, renewable and environmental stocks is the NNP function. Routine substitutions reveal that the using up of natural resource stocks is representable as an easy-to-interpret economic depreciation magnitudes. We obtain true NNP inclusive of natural resource stock diminution.
Keywords: 330